Sphaeranthus senegalensis DC: Evaluation of chemical constituents, oral safety, gastroprotective activity, and mechanism of action of its hydroethanolic extract. (25th March 2021) - Sudi, Ismaila Yada; Ahmed, Maryam Usman; Adzu, Bulus
Abstract: Ethnopharmacological relevance: Sphaeranthus senegalensis DC is a seasonal herb with a spicy smell that grows wild in wet grounds of tropical Africa and Asia. The plant is used in folk medicine for the treatment of various diseases; that includes its use to treat gastric ulcers. Aim of the study: This study aimed to investigate the chemical constituents of the hydroethanolic extract of Sphaeranthus senegalensis DC and evaluate its oral safety, gastroprotective activity, and mechanisms of action using laboratory models in rats and mice. Materials and methods: Hydroethanolic extract (70%) of the powdered whole dried material was prepared, and chemical constituents of the resultant extract (denoted HESs) standardized using the high-performance liquid chromatography (HPLC) method. The safety profile of HESs was assessed using 2000 mg/kg, oral (p.o.) for Hippocratic screening in mice, and 800 mg/kg, p.o. for 28 days subchronic toxicity assay in rats. The gastroprotective effect of HESs (25, 100, and 400 mg/kg, p.o.) was investigated using acidified ethanol, piroxicam, water immobilization stress, and acetic acid-induced ulcer models. The gastroprotective mechanisms of HESs were evaluated using its effect on gastric mucus protection, nitric oxide modulation, gastric juice secretory parameters, catalase and myeloperoxidase activities. Histological analysis of the stomach tissues was also carried out. Results: The HPLC analysis indicated the presence of 25.94% phenolics (gallic acid, caffeic acid, and ferulic acid) and 14.53% flavonoids (rutin, morin, luteolin, quercetin, and apigenin). Hippocratic screening and the 28 days subchronic study indicated that HESs is generally safe. Result shows that oral administration of HESs (25, 100 and 400 mg/kg) alleviated the severity of the gastric ulcers induced by acidified ethanol by 35.65% ( p < 0.05), 48.70% ( p < 0.05) and 78.02% ( p < 0.001) respectively; exhibited gastroprotective effect against the gastric lesions induced by piroxicam by 37.97% ( p < 0.05), 53.27% ( p < 0.05) and 76.23% ( p < 0.001) respectively; and decreased the severity of the water immobilization stress-induced gastric ulcers by 32.43% ( p < 0.05), 55.26% ( p < 0.01) and 74.05% ( p < 0.001) respectively, when compared to the vehicle control group. The mechanisms of action assays indicated that the gastroprotective activity was mediated mainly through gastroprotection, antisecretory, and antioxidant activities. Histological analysis showed it inhibited epithelial cell loss, vascular damage, and leucocyte infiltration. Conclusion: HESs contains useful phytochemicals, is safe, and exhibited significant gastroprotective action. The results provided justification for its claim in the treatment of gastric ulcers and its evaluation for potential application as a gastroprotective agent. Graphical abstract: Image 1